O espetáculo de imagens na ordem do discurso midiático: o corpo em cena na revista Veja. - Pereira., Tânia Maria Augusto (2013)
This thesis investigates the spectacularization of the body in the media. The object of our research is the discourse on the body and its senses can be analyzed on the covers of the Veja magazine that address the cult of the body. Based on the assumption the understanding of the body as a discursive event spectacularized, as a historical and cultural construction, on which articulate different discourses and knowledge, we aimed to assess how the body is discursively constructed by Veja magazine. Therefore, we seek to clarify which body this magazine spectacularized over its 44 years of publication and which bodies were excluded. We also seek to reflect on how the discourse of the magazine is meant, legitimated, acknowledged and maintained through disciplinary techniques used to train the body, within what Michel Foucault calls Biopolitics. Theoretically, this work is part of the third season of Discourse Analysis, a period marked by a dialogue between the thoughts of Michel Pecheux and Michel Foucault. In addition to the contributions of Foucault, in its analytical power, theories of speech, we also support the discursive formulations of Jean-Jacques Courtine (2005, 2006, 2008, 2009a, 2009b), in the field of Cultural Studies, represented by Bauman (2001, 2005), Hall (2003, 2006), Silva (2003), among others, and the notion of spectacle, as developed by Guy Debord (1997). The media is configured as a disciplining device, as it creates identities and assumes that such identities are effects of speech, since it is within the discursive practices they emerge. Taking care of yourself means taking care of the contemporary body feel good from rules of conduct and principles imposed truths and prescriptions as constructed by the media through exposure incessant images of beautiful bodies. We note the work on the covers of disciplinary mechanisms that dictate forms and habits of life framed in power / knowledge. The bodies presented by the discourse of ordering one magazine saying that goes beyond the aesthetic beauty, since such discourse produces, stabilizes and circulates a beam directions, materializing sayings sustained by discursive memory, deleting or leaving implicit others.